Uso do Barômetro da Sustentabilidade Para Avaliação de um Município Localizado em Região Semiárida do Nordeste Brasileiro - Aline de Souza Amorim (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
The increase in economic and industrial activities has resulted in the emergence of environmental problems that affect the quality of life triggers thus a crisis in relations between society and environ - ment. In this context of cultural changes, social and environmental arises the concept of sustainable development and with it the sustainability indicators, which through various aggregate indices, have a central role in decision-making process, ie, the transformation of information into concrete actions aimed at the collective interest. Attending to this, this study aimed to assess the sustainability of the city of Caic ó – RN through the application of the Barometer of Sustainability and from the results to an analysis of how they can influence the quality of the water supply of the municipality. Performance scales were made of the municipality and the results were treated and placed in relative scales ranging from 0 to 100. The results indicate that Caicó occupies a potentially unsustainable according to the methodology of the tool, requiring, therefore, of public policies that improve this situation.